2001
DOI: 10.1242/dev.128.21.4203
|View full text |Cite
|
Sign up to set email alerts
|

EGFRs mediate chemotactic migration in the developing telencephalon

Abstract: Epidermal growth factor receptors (EGFRs) have been implicated in the control of migration in the telencephalon, but the mechanism underlying their contribution is unclear. We show that expression of a threshold level of EGFRs confers chemotactic competence in stem cells, neurons and astrocytes in cortical explants. This level of receptor expression is normally achieved by a subpopulation of cells during mid-embryonic development. Cells that express high levels of EGFR are located in migration pathways, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The LCS populates the basal telencephalic limbic system, in particular the piriform and olfactory cortices and the amygdala (Hirata et al 2002;Carney et al 2006, Bai et al 2008. The PSB also seeds the embryonic and postnatal SVZ stem cell niche and their subsequent progeny that migrate along the RMS to generate diverse subtypes of OB interneurons (Waclaw et al 2006;Kohwi et al 2007) Our analysis of EGFR expression, a previously identified marker of LCS migratory cells (Caric et al 2001), reveals that both the subpallial (Dlx2+) and pallial (Pax6+) subpopulations are both EGFR+. As Tgfa, a known ligand for EGFR, is expressed in the VP, it is possible that this signaling pathway is required for specification/migration of EGFR+ cells of the LCS.…”
Section: Function Of Pax6 and Gsh2 In The Specification Of The Psb Pr...mentioning
confidence: 80%
See 1 more Smart Citation
“…The LCS populates the basal telencephalic limbic system, in particular the piriform and olfactory cortices and the amygdala (Hirata et al 2002;Carney et al 2006, Bai et al 2008. The PSB also seeds the embryonic and postnatal SVZ stem cell niche and their subsequent progeny that migrate along the RMS to generate diverse subtypes of OB interneurons (Waclaw et al 2006;Kohwi et al 2007) Our analysis of EGFR expression, a previously identified marker of LCS migratory cells (Caric et al 2001), reveals that both the subpallial (Dlx2+) and pallial (Pax6+) subpopulations are both EGFR+. As Tgfa, a known ligand for EGFR, is expressed in the VP, it is possible that this signaling pathway is required for specification/migration of EGFR+ cells of the LCS.…”
Section: Function Of Pax6 and Gsh2 In The Specification Of The Psb Pr...mentioning
confidence: 80%
“…Alterations in LCS cell migration in Gsh2, Sey, and Sey/ Gsh2 double mutants at E15.5 To examine defects in cell migration along the LCS in Gsh2, Sey, and Sey/Gsh2 double mutant mice, we carried out immunohistochemical analysis for EGFR, which is expressed at the PSB and in migrating cells of the LCS (Caric et al 2001). First, we further characterized the cell types of the PSB that express EGFR.…”
Section: Interneuron Markers Dlx2 and Dlx5mentioning
confidence: 99%
“…EGFR is essential for growth and differentiation in various developing systems, including the nervous system (Caric et al , 2001; Xian & Zhou, 2004; Chen et al , 2016; Romano & Bucci, 2020). Here, we found that EGFR‐expressing transitional glial cells were present and exhibited a radial morphology at the onset of gliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signaling generally regulates cell proliferation, growth, differentiation and cell survival ( Oda et al, 2005 ). In the developing brain, the EGFR is increasingly expressed over time ( Romano and Bucci, 2020 ) and is mainly found in proliferating and migratory brain regions ( Kornblum et al, 1997 ; Caric et al, 2001 ). The EGFR is therefore indispensable for proper rodent brain development ( Romano and Bucci, 2020 ).…”
Section: Resultsmentioning
confidence: 99%